Needs and Experiences in Psychiatric Treatment (NEPT)- Piloting a Collaboratively Generated, Initial Research Tool to Evaluate Cross-Sectoral Mental Health Services - von Peter, Sebastian; Krispin, Helene; Kato Glück, Rosa; Ziegenhagen, Jenny; Göppert, Lena; Jänchen, Patrick; Schmid, Christine; Neumann, Anne; Baum, Fabian; Soltmann, Bettina; Heinze, Martin; Schwarz, Julian; et al. (Frontiers in Psychiatry, 2022)
Background Research tools to evaluate institutions or interventions in the field of mental health have rarely been constructed by researchers with personal experience of using the mental health system (“experiential expertise”). This paper presents a preliminary tool that has been developed within a participatory-collaborative process evaluation as part of a controlled, multi-center, prospective cohort study (PsychCare) to evaluate psychiatric flexible and integrative treatment, FIT for short, models in Germany. Method The collaborative research team consisting of researchers with and without experiential expertise developed 12 experiential program components of FIT models by an iterative research process based on the Grounded Theory Methodology. These components were transformed into a preliminary research tool that was evaluated by a participatory expert panel, and during a pilot and validation study, the latter using a random sample of 327 users from 14 mental health departments. Internal consistency of the tool was tested using Cronbach's alpha. Construct validity was evaluated using a Principal Components Analysis (PCA) and a Jonckheere Terpstra test in relation to different implementation levels of the FIT model. Concurrent validity was tested against a German version of the Client Satisfaction Questionnaire (ZUF-8) using correlation analysis and a linear regression model. Results The evaluation of the expert panel reduced 29 initial items to 16 that were further reduced to 11 items during the pilot study, resulting into a research tool (Needs and Experiences in Psychiatric Treatment—NEPT) that demonstrated good internal consistency (Cronbach's alpha of 0.89). PCA yielded a 1-component structure, which accounted for 49% of the total variance supporting the unidimensional structure of the tool. The total NEPT score increased alongside the increasing implementation of the FIT model (p < 0.05). There was evidence (p < 0.001) for convergent validity assessed against the ZUF-8 as criterion measure. Conclusions The NEPT tool seems to be promising for further development to assess the experiences with and fulfillment of needs of psychiatric care models from the perspective of users. This paper demonstrates that it is possible to use a participatory-collaborative approach within the methodologically rigorous confines of a prospective, controlled research design.